2008
DOI: 10.1086/590674
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Networks if Everyone Strives for Structural Holes

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
142
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(154 citation statements)
references
References 44 publications
10
142
0
2
Order By: Relevance
“…For example, social capital researchers often assume that goal-oriented actors seek out different network positions for the benefits those positions provide. More recent research has shown, however, that network-based benefits cannot be sustained when all actors share the primary objective of achieving those benefits and these objectives are common knowledge (Ryall and Sorenson, 2007;Buskens and van de Rijt, 2008). Our findings reinforce this lesson for a different but related reason.…”
Section: Discussionsupporting
confidence: 82%
“…For example, social capital researchers often assume that goal-oriented actors seek out different network positions for the benefits those positions provide. More recent research has shown, however, that network-based benefits cannot be sustained when all actors share the primary objective of achieving those benefits and these objectives are common knowledge (Ryall and Sorenson, 2007;Buskens and van de Rijt, 2008). Our findings reinforce this lesson for a different but related reason.…”
Section: Discussionsupporting
confidence: 82%
“…they can tie cohesive network communities together into a small-world social system; impact the availability of entrepreneurial opportunities in the network; and affect the stratification of social systems (Buskens and Van de Rijt 2008). Thus, understanding the determinants of bridging ties, which has been the thrust of this study, sheds additional light on the complex, multi-level dynamics of how complex social systems arise and evolve.…”
Section: Discussionmentioning
confidence: 92%
“…The statement, also applies to any refinement of pairwise stability, e.g. bilateral stability (Goyal and Vega-Redondo 2007), unilateral stability (Buskens and van de Rijt 2008), strong stability (Dutta and Mutuswami 1997), and weak stability (Dutta and Mutuswami 1997). Moroever, for the notion of pairwise stability with transfers it is possible to state a similar result, which is however restricted to the utilitarian welfare function.…”
Section: Definition 5 a Utility Function U I Is Concave (In Own Linksmentioning
confidence: 98%